Photon avalanche in nanoluminophore obtained by REE silicate evaporation - M.G. Zuev (Elsevier, 2021)
A bulk phosphor composition Sr2Y6.8YbEr0.2Si6O26 was synthesized. A nanophosphorus in an amorphous state was obtained from this sample by the method of pulsed electron beam evaporation. The spectra of upconversion photoluminescence of bulk and nanosamples were studied. In the field of pumping power of nanosample with 78 mW laser radiation with a wavelength of 980 nm, there is a threshold population of energy levels Er3+. Laser radiation carries out resonant pumping of 4I13/2 → 4F9/2 transition. Then there is an intensive red radiation upon transition 4F9/2 → 4I15/2. A photon avalanche was found in the nanophosphore, at which the intensity of red radiation increases ∼80 times compared to the bulk phosphorus.